Pengaruh Konsentrasi Lidokain Terhadap Bakteri Streptococcus Mutans - Haryon, Muhammad Wildan Hari Subagya; Rahayoe, Poerwati Soetji (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
Lidocaine is one of local anaesthesia agent that has antibacterial power: Streptococcus mutans are normal bacterium in oral cavity. The purpose of this research are for knowing the effect of lidocaine concentration in inhibiting and killing power to Streptococcus mutans. The research design use eksperimental design, with dilution liquid and solid method which used to know inhibiting power and or killing power concentration sample. Bacterial test that used in this research has been compared with McFarland standard liquid with has concentration of] 0‘ CF U/ML. The samples concentration are 2%, I %, 0,5 %, 0,25%, 0, 125%, 0,0625%, 0,03125%, 0, 01 5625%, 0, 00781 2%. Statistic test by Kruskal-Wallis and Mann- Whitney.The research result said that there is a relation between lidocaine concentration with Streptococcus mutans bacterial with inhibiting power on 2 %, I % and 0,5 % and with minimal inhibiting activity at 0,5% (p0,05). There is no result about killing power in lidocaine concentration to Streptococcus mutans bacterial ( p0, 05).